Combating Wear of ASTM A36 Steel by Surface Modification Using Thermally Sprayed Cermet Coatings - Vineet Shibe; Vikas Chawla (Advances in Materials Science and Engineering)
Thermal spray coatings can be applied economically on machine parts to enhance their requisite surface properties like wear, corrosion, erosion resistance, and so forth. Detonation gun (D-Gun) thermal spray coatings can be applied on the surface of carbon steels to improve their wear resistance. In the present study, alloy powder cermet coatings WC-12% Co and Cr3C2-25% NiCr have been deposited on ASTM A36 steel with D-Gun thermal spray technique. Sliding wear behavior of uncoated ASTM A36 steel and D-Gun sprayed WC-12% Co and Cr3C2-25% NiCr coatings on base material is observed on a Pin-On-Disc Wear Tester. Sliding wear performance of WC-12% Co coating is found to be better than the Cr3C2-25% NiCr coating. Wear performance of both these cermet coatings is found to be better than uncoated ASTM A36 steel. Thermally sprayed WC-12% Co and Cr3C2-25% NiCr cermet coatings using D-Gun thermal spray technique is found to be very useful in improving the sliding wear resistance of ASTM A36 steel.